AN INVESTIGATION INTO OPEN-ENDED QUESTION PREPARATION SKILLS OF TURKISH LANGUAGE TEACHERS - Osman Mert; Orhan Özen (Educational Academic Research, 2024)
This study aimed at determining to what extent Turkish teachers prepare open-ended questions and how often they use this type of questions. Another purpose is to present suggestions about the problems that teachers face when preparing open-ended questions. This study is a case study which is one of the qualitative research methods. Semi-structured interview was performed with teachers who prepared written exams including open-ended questions. Descriptive analysis was used to analyze the data obtained at the end of the interview. The participants of the interview are 13 Turkish language teachers working in 7 secondary schools in Tortum district of Erzurum. With the permission obtained from the Erzurum Provincial Directorate of National Education, samples of written exam papers consisting of open-ended questions used in the 5th, 6th, 7th and 8th grades of the Turkish teachers working in 7 secondary schools in Tortum district were taken in the 2018-2019 and 2019-2020 academic years. Written exam samples including open-ended questions used in this study were analyzed using the document review method. The findings obtained from the interviews showed that teachers faced problems in preparing and scoring open-ended questions due to insufficient time, scope validity, and evaluation. Also, it was found that open-ended questions measure lower-level skills such as remembering, comprehending and applying in terms of cognitive domain learning and consist of simple reading comprehension questions. The results of the study revealed that teachers are aware of the importance of open-ended questions in Turkish lessons, they use open-ended questions in their exams adequately, although their ability to prepare open-ended questions is low. When examined open-ended questions prepared by teachers, it was found that these types of questions were mostly prepared in the form of simple reading comprehension questions and they were included in the lower levels of cognitive domain. The study also revealed that the reliability of the questions was low, since a detailed answer key was not generally used in the scoring of the questions. Preparing questions that only measure the learning outcomes in terms of reading may reduce validity. Turkish language teaching, assessment and evaluation, open-ended questions.